Impact of Serum Amylase Level in the Outcome of Acute Organophosphorus Poisoning: 2-Year Cross-Sectional Study at Rural Teaching Hospital - Patil, Aniket; Kumar, Sunil; Inamdar, Anil; Acharya, Sourya; Wanjari, Anil; Bawankule, Shilpa; Agrawal, Sachin; Sontakke, Tushar (Journal of Laboratory Physicians, 2021)
Introduction Prompt recognition and aggressive management of acute intoxication due to organophosphorus poisoning are essential to minimize the morbidity and mortality. The present study was undertaken to know the prognosis and outcome of organophosphorus poisoning patients with the estimation of low-cost enzymes like the serum amylase level in a population with financial constraints.Methods In this cross-sectional study, we had enrolled 100 cases that had a history of exposure to organophosphorus compounds, and the serum amylase level was measured in all the patients. We assessed the outcome of all the patients in the form of discharge, need of ventilators, intensive care unit stay, and death.Results The mean serum amylase level in discharge patients was 335.40 ± 192.45, and in the patients who died it was 843.37 ± 22.60. It was significant to predict the outcome (t-value 7.07, p-value 0.0001, statistically significant).Conclusion Serum amylase level shows significant correlation with clinical outcomes in organophosphorus poisoning.
Keywords: serum amylase; organophosphorus poisoning; outcome; serum acetylcholinesterase